Characterisation of strip silicon detectors for the ATLAS Phase-II Upgrade with a micro-focused X-ray beam. (29th July 2016) - Poley, L.; Blue, A.; Bates, R.; Bloch, I.; Díez, S.; Fernandez-Tejero, J.; Fleta, C.; Gallop, B.; Greenall, A.; Gregor, I.-M.; Hara, K.; Ikegami, Y.; et al.
Abstract: The planned HL-LHC (High Luminosity LHC) in 2025 is being designed to maximise the physics potential through a sizable increase in the luminosity up to 6·10 34 cm −2 s −1 . A consequence of this increased luminosity is the expected radiation damage at 3000 fb −1 after ten years of operation, requiring the tracking detectors to withstand fluences to over 1·10 16 1 MeV n eq /cm 2 . In order to cope with the consequent increased readout rates, a complete re-design of the current ATLAS Inner Detector (ID) is being developed as the Inner Tracker (ITk). Two proposed detectors for the ATLAS strip tracker region of the ITk were characterized at the Diamond Light Source with a 3 μ m FWHM 15 keV micro focused X-ray beam. The devices under test were a 320 μ m thick silicon stereo (Barrel) ATLAS12 strip mini sensor wire bonded to a 130 nm CMOS binary readout chip (ABC130) and a 320 μ m thick full size radial (end-cap) strip sensor - utilizing bi-metal readout layers - wire bonded to 250 nm CMOS binary readout chips (ABCN-25). A resolution better than the inter strip pitch of the 74.5 μ m strips was achieved for both detectors. The effect of the p-stop diffusion layers between strips was investigated in detail for the wire bond pad regions. Inter strip charge collection measurements indicate that the effective width of the strip on the silicon sensors is determined by p-stop regions between the strips rather than the strip pitch.